Application of Molecular Cytogenetic Technique for Rapid Prenatal Diagnosis of Aneuploidies in Iranian Population - Habib Nasiri; Jila Dastan; Mohammad Hasan Seifi; Noori Dalooi; Saeed Reza Ghaffari (Tehran University of Medical Sciences, 2009)
Objective: Classic cell culture and karyotyping is routinely used for prenatal detection of different chromosomal abnormalities. Molecular cytogenetic techniques have also recently been developed and used for this purpose. Quantitative florescence PCR using short tandem repeat (STR) markers has more potential for high throughput diagnosis. Marker heterozygosity in short tandem repeats (STR) is of critical importance in the clinical applicablity of this method. Materials and Methods: Different STR markers on chromosomes 13, 18, 21, X and Y  were analysed from  amniotic samples to detect related disorders such as Down, Edward, Patau,  Klinefelter sundromes , as well as sex chromosomes numerical abnormalities . Results: In our population some markers (D18S976, DXS6854, D21S11, and D21S1411) showed alleles with sizes out of expected ranges. But others occupied narrower range of predicted distribution. Most markers have enough heterozygosity (66.3-94.7) to be used for prenatal diagnosis. Furthermore, results obtained from full karyotype for all samples were in concordance with results of molecular cytogenetic testing. Conclusion: It is concluded that, in urgent situations, if proper markers used, molecular cytogenetic testing (QF-PCR) could be a useful method for rapid prenatal diagnosis (PND) in populations with high rate of consanguinity such as Iran.